Women, power, gender and self : a discourse analysis approach : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University - Anderson, Karen P (Massey University, 1994)
Previous research that has provided information about the concepts of power and self has come largely from the traditional empiricist paradigm. This research generally reflects the notion that there are different kinds of power which are equated with masculinity and femininity. In general, power based settings and women are viewed as incompatible. Sense of self has been traditionally presented in the research as something identifiable and consistent. Gender is a thread that runs through the research and the literature on both power and identity, and it is a constructive part of our understanding of them. This study uses a qualitative approach to look at the accounts of ten women in terms of power and how this relates to their sense of self. Potter and Wetherell's (1987) model of discourse analysis has been used in analysing the research interviews. The results of the study tend to support Potter and Wetherell's contention that "self" will be constructed in various ways depending upon context. It also appears that these constructions are inextricably linked with power and gender. Trait and role discourses are used by the women and described in the study. The function of each enables the women to talk about different presentations of "self" that do not contravene the dominant discourses when discussing themselves and power.
Keywords: Sex role; Employment -- Psychological aspects; Women; Psychology; Social psychology